الاتصال الغير رسمي و علاقته بادارة الصراع التنظيمي - رانيا بهلولي; خديجة بن معاش; د/ المداني حجاج (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: جاءت دراستنا بعنوان الاتصال غير الرسمي وعلاقته بإدارة الصراع التنظيمي "دراسة حالة مؤسسة CNAS الأغواط . وانطلقت دراستنا من الإشكالية: هل يؤثر الاتصال غير الرسمي في ادارة الصراع؟ وتتفرع الإشكالية العامة للدراسة إلى مجموعة من التساؤلات الفرعية تتمثل في: - هل توجد مظاهر الاتصال غير الرسمي في المؤسسة؟ - كيف هي إجراءات التحكم في إدارة الصراع داخل المؤسسة؟ - هل لتواجد الاتصال غير الرسمي تأثير في إدارة الصراع داخل المؤسسة؟ نهدف من خلال دراستنا الى التعرف على دور الاتصال غير رسمي في إدارة الصراع بمؤسسة الصندوق الوطني للتأمينات الاجتماعية للأجراءCNAS بالأغواط، وفي دراستنا اعتمدنا على المنهج الوصفي وأداة جمع البيانات تمثلت في الاستبيان لدراسة مجتمع الدراسة المتكون من 100عاملا بالمؤسسة حيث توصلنا الى النتائج التالية: 1. عمال مؤسسة الصندوق الوطني للتأمينات الاجتماعية للأجراءCNAS بالأغواط يستعنون بزملائهم في مجال العمل من اجل تبادل الخبرات والتعاون فيما بينهم من اجل مصلحة المؤسسة 2. ادارة مؤسسة الصندوق الوطني للتأمينات الاجتماعية للأجراءCNAS بالأغواط تتدخل في حال وجود الصراع لحل بطريقة رسمية ولكن احيانا تحل الصراع بطريقة غير رسمية. 3. الاتصالات الغير رسمية هي الأكثر استخداما في مؤسسة الصندوق الوطني للتأمينات الاجتماعية للأجراءCNAS بالأغواط . 4. عمال مؤسسة الصندوق الوطني للتأمينات الاجتماعية للأجراءCNAS بالأغواط يلتقون بعظهم البعض خارج المؤسسة حسب علاقاتهم داخل المؤسسة ومعظم احاديثهم عن الالتقاء تدور حول مجال العمل. Study summary Our study was titled “The Role of Professional Applications in Creating Communication Coordination within the Institution,” a Case Study of the CNAS Laghouat Foundation Our study started from the problem: Does informal communication affect conflict management? The general problem of the study is divided into a set of sub-questions:  Are there aspects of informal communication in the organization?  How are the procedures for controlling conflict management within the organization? Does the presence of informal communication have an impact on conflict management within the organization? Through our study, we aim to identify the role of informal communication in conflict management at the National Fund for Social Insurance for Labour’s Foundation (CNAS) in Laghouat. In our study, we relied on the descriptive approach and the data collection tool represented by the questionnaire to study the study population consisting of 100 workers in the institution, where we reached the following results: 1. Workers at the National Fund for Social Insurance for Labours (CNAS) in Laghouat seek help from their colleagues in the field of work in order to exchange experiences and cooperate among themselves for the benefit of the institution. 2. The management of the National Fund for Social Insurance for Labour’s CNAS in Laghouat intervenes in the event of a conflict to resolve it in an official manner, but sometimes the conflict is resolved informally. 3. Informal communications are the most used in the National Fund for Social Insurance Foundation for employees (CNAS) in Laghouat. 4. Workers at the National Fund for Social Insurance for Employees (CNAS) in Laghouat meet each other outside the institution according to their relationships within the institution, and most of their conversations about the meeting revolve around the field of work.
بالاغواط CNASدراسة حالة في الصندوق الوطني للتامينات الاجتماعية للاجراء